A positive attitude among primary healthcare providers predicts better hepatitis B prevention practices: evidence from a cross-sectional survey in Wakiso district, Central Uganda - Tonny Ssekamatte; John Bosco Isunju; Paul Alex Kimoga Zirimala; Samuel Etajak; Saul Kamukama; Mathias Seviiri; Mary Nakafeero; Aisha Nalugya; Solomon Tsebeni Wafula; Edwinah Atusingwize; Justine. N. Bukenya; Richard K. Mugambe (Health Psychology and Behavioral Medicine, 2021)
Background: Hepatitis B Virus (HBV) infection is an important occupational health risk among primary healthcare providers (PHCPs). However, there is limited evidence on whether PHCPs’ level of knowledge and attitude can predict better HBV infection prevention practices. This study established the relationship between knowledge, attitude, and HBV infection prevention practices among PHCPs in Wakiso district, Central Uganda. Methods: A cross-sectional study design was used. Data were collected from 306 PHCPs, using a structured questionnaire. PHCPs were randomly selected from 55 healthcare facilities. STATA version 14.0 was used to analyse data. A ‘modified Poisson’ regression model was used for inferential statistics. Results: About 42.2% of PHCPs exhibited poor knowledge of HBV infection transmission and prevention, 41.8% had a negative attitude, and 41.5% exhibited poor prevention practices. Age (PR 1.82, 95% CI: 1.24–2.66) was positively associated with the level of knowledge. Healthcare facility level (PR 0.53, 95% CI: 0.34–0.84), main department of work (PR 0.69, 95% CI: 0.51–0.95), years in service (PR 0.66, 95% CI: 0.44–0.99), working in private not-for-profit healthcare facilities (PR 0.59, 95% CI: 0.34–0.99), and public healthcare facilities (PR 0.58, 95% CI: 0.42–0.80) were negatively associated with the level of knowledge. There was a negative association between the location of healthcare facility (PR 0.76, 95% CI: 0.62–0.93) and attitude, and a positive association between level of knowledge (PR 1.36, 95% 1.12–1.65) and attitude. Working in a public healthcare facility (PR 0.80, 95% CI: 0.64–0.99) was negatively associated with practices while having a positive attitude (PR 1.60, 95% CI: 1.28–1.99) predicted better HBV infection prevention practices. Conclusion: PHCPs who were more knowledgeable about HBV infection were more likely to have a positive attitude. In turn, having a positive attitude was associated with better HBV infection prevention practices. There is a need to sensitise PHCPs on HBV infection, and provision of screening and vaccination services in order to address the KAP gaps.